Implementation of the Speaking Etiquette Program in Islamic Religious Education Learning for Phase B Elementary School Students - Wersi Anggraini; Nesia Andriana; Santi Lisnawati (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of the speaking etiquette (adab al-kalam) program for Phase B primary school students (grades 3-4) from an Islamic educational perspective, as well as its impact on students' communication behavior. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation at SD Muhammadiyah 02 Cileungsi, Bogor. The results indicated that the speaking etiquette program was implemented by integrating Quranic and Hadith values with pedagogical methods such as modeling, role-playing, and positive reinforcement. This program had a significant impact on improving students' communication behavior, characterized by increased use of polite language, active listening skills, and interpersonal empathy. The primary challenges identified were the consistency of application outside the school environment and the varying levels of parental involvement. This study concludes that optimal development of speaking etiquette in Phase B is highly dependent on the synergy between teacher role-modeling and continuous reinforcement from the family environment. The implication is that this program can serve as a systematic character education curriculum model for Islamic elementary schools to mitigate the negative impacts of communication in the digital era.